Brg1 loss attenuates aberrant wnt-signalling and prevents wnt-dependent tumourigenesis in the murine small intestine. - Aliaksei Z Holik; Madeleine Young; Joanna Krzystyniak; Geraint T Williams; Daniel Metzger; Boris Y Shorning; Alan R Clarke (PLoS Genetics, 2014)
Tumourigenesis within the intestine is potently driven by deregulation of the Wnt pathway, a process epigenetically regulated by the chromatin remodelling factor Brg1. We aimed to investigate this interdependency in an in vivo setting and assess the viability of Brg1 as a potential therapeutic target. Using a range of transgenic approaches, we deleted Brg1 in the context of Wnt-activated murine small intestinal epithelium. Pan-epithelial loss of Brg1 using VillinCreERT2 and AhCreERT transgenes attenuated expression of Wnt target genes, including a subset of stem cell-specific genes and suppressed Wnt-driven tumourigenesis improving animal survival. A similar increase in survival was observed when Wnt activation and Brg1 loss were restricted to the Lgr5 expressing intestinal stem cell population. We propose a mechanism whereby Brg1 function is required for aberrant Wnt signalling and ultimately for the maintenance of the tumour initiating cell compartment, such that loss of Brg1 in an Apc-deficient context suppresses adenoma formation. Our results highlight potential therapeutic value of targeting Brg1 and serve as a proof of concept that targeting the cells of origin of cancer may be of therapeutic relevance.